Resveratrol Downregulates Interleukin-6-Stimulated Sonic Hedgehog Signaling in Human Acute Myeloid Leukemia. (20th February 2013) - Su, Yu-Chieh; Li, Szu-Chin; Wu, Yin-Chi; Wang, Li-Min; Chao, K. S. Clifford; Liao, Hui-Fen
Abstract : IL-6 and sonic hedgehog (Shh) signaling molecules are considered to maintain the growth of cancer stem cells (CSCs). Resveratrol, an important integrant in traditional Chinese medicine, possesses certain antitumor effects. However, the mechanisms on regulating acute myeloid leukemia (AML) are unclear. This study first used human subjects to demonstrate that the plasma levels of IL-6 and IL-1 β in AML patients were higher and lower, respectively, than healthy donors. The expression of Shh preproproteins, and C- and N-terminal Shh peptides increased in bone marrow and peripheral blood mononuclear cells isolated from AML patients, and the plasma N-Shh secretion was greater. To further clarify the effect of IL-6 and resveratrol in Shh signaling, human AML HL-60 cells were tested. IL-6 upregulated Shh and Gli-1 expression and was accompanied by an increase of cell viability. Resveratrol significantly decreased CSC-related Shh expression, Gli-1 nuclear translocation, and cell viability in IL-6-treated HL-60 cells and had synergistic effect with Shh inhibitor cyclopamine on inhibiting cell growth. Conclusions . IL-6 stimulated the growth of AML cells through Shh signaling, and this effect might be blocked by resveratrol. Further investigations of Shh as a prognostic marker and resveratrol as a therapeutic drug target to CSCs in AML are surely warranted.